IRGD‐modified exosomes effectively deliver CPT1A siRNA to colon cancer cells, reversing oxaliplatin resistance by regulating fatty acid oxidation. Issue 12 (22nd July 2021) - Lin, Dan; Zhang, Haiyang; Liu, Rui; Deng, Ting; Ning, Tao; Bai, Ming; Yang, Yuchong; Zhu, Kegan; Wang, Junyi; Duan, Jingjing; Ge, Shaohua; Sun, Bei; et al.
Abstract : Fatty acid oxidation (FAO) plays a vital role in drug resistance in cancer cells. Carnitine palmitoyltransferase 1A ( CPT1A ), a key enzyme of FAO, is widely recognized as an emerging therapeutic target. Here, we confirmed that CPT1A was heterogeneously expressed in colon cancer cells, with a high expression in oxaliplatin‐resistant cells but low expression in oxaliplatin‐sensitive cells, and expression could be increased by oxaliplatin stimulation. In addition, we verified that CPT1A was more highly expressed in colon cancer tissues than in noncancerous tissues. Silencing CPT1A by siRNA or etomoxir, a specific small‐molecule inhibitor of CPT1A, could reverse the sensitivity of drug‐resistant colon cancer cells to oxaliplatin. Subsequently, the combination of oxaliplatin with CPT1A inhibition promoted apoptosis and inhibited proliferation. In addition, exosomes were generated with the iRGD peptide on the surface, which showed highly efficient targeting compared with control exosomes in vivo . Furthermore, we loaded and therapeutically applied iRGD‐modified exosomes with si CPT1A to specifically deliver si CPT1A into tumours to suppress FAO. As a consequence, iRGD‐modified exosomes showed the significant inhibition of CPT1A in tumour tissues and exhibited the ability to reverse oxaliplatin resistance and inhibit tumour growth by inhibiting FAO with high safety in vivo . Abstract : Fatty acid oxidation (FAO) plays a vital role in drug resistance in cancer cells. High expression of Carnitine palmitoyltransferase 1A ( CPT1A ), a key enzyme in FAO, was observed in colon cancer tissues. Here, we demonstrated that silencing of CPT1A by iRGD‐exosome‐si CPT1A efficiently suppressed FAO, inhibited tumorigenesis and reversed oxaliplatin resistance in colon cancer. Altogether, iRGD‐exosome‐si CPT1A mediated silencing of FAO may serve as an effective approach to treat oxaliplatin‐resistant patient with colon cancer and may propel the clinical application of iRGD‐engineered exosomes for siRNA delivery in cancer treatment.